1996
DOI: 10.1046/j.1365-2362.1996.108250.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective interferon‐gamma production by T‐lymphocytes from patients with acute brucellosis

Abstract: The authors investigated the production of interleukin-2 (IL-2) and interferon-gamma (IFN-gamma) by phytohaemagglutinin (PHA)-stimulated T-lymphocytes from 21 untreated patients with acute brucellosis. PHA-stimulated T-lymphocytes from acute brucellosis patients showed normal IL-2 production but defective IFN-gamma production (brucellosis patients 531 +/- 103 pg mL-1 vs. healthy controls 1024 +/- 212 pg mL-1) after 72 h of culture. This altered pattern of IL-2 and IFN-gamma production by T-lymphocytes was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…The finding of enhanced intracytoplasmic IFN-␥ expression in T lymphocytes from brucellosis patients agrees with the increased serum cytokine levels observed (1,27). We previously found decreased IFN-␥ production by phytohemagglutinin (PHA)-stimulated T-lymphocyte-enriched cultures (46). PHA is a monocyte-dependent mitogen (50).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The finding of enhanced intracytoplasmic IFN-␥ expression in T lymphocytes from brucellosis patients agrees with the increased serum cytokine levels observed (1,27). We previously found decreased IFN-␥ production by phytohemagglutinin (PHA)-stimulated T-lymphocyte-enriched cultures (46). PHA is a monocyte-dependent mitogen (50).…”
Section: Discussionsupporting
confidence: 79%
“…Several abnormalities in the immune system have been found in human brucellosis (27,46,49). It has been found that T and NK lymphocytes show defective functions in brucellosis patients (46,49). Since mice are naturally resistant to Brucella infections, it is possible to suggest that the immune response elicited by Brucella in humans might have different characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B. abortus, as well as L-Omp19 and Pam 3 Cys, also diminished MHC-II expression and inhibited the ability of human monocytes to process and present soluble Ags (PPD) to polyclonal T cells from human donors. The finding that Brucella lipoproteins inhibited the ability of human monocytes to activate Agspecific T cells suggests that these molecules could be implicated in the down-modulation of T-cell responses reported in human brucellosis (24,33,45,46). Indeed, our results indicate that prolonged exposure to Pam 3 Cys of PBMCs from acute patients, which display a Th1-type response with cell proliferation and production of IFN-␥ and IL-2, transforms this response towards the nonresponder phenotype of chronically infected patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…Some cytokines can regulate the immune system and play key roles on the outcome of brucellosis. Several studies have shown that T cell proliferation and Th1 cytokine production are reduced in brucellosis (5,6). Interferon-gamma (IFN-γ) is a well-studied cytokine (2,5,7,8).…”
Section: Brucellosis Is Endemic In Many Middlementioning
confidence: 99%